2021
DOI: 10.1093/bjs/znab017
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after surgery for primary hyperparathyroidism: results from a nationwide cohort

Abstract: Background Contemporary patients with primary hyperparathyroidism are often diagnosed with mildly raised serum calcium levels. Previous studies have reported increased mortality in patients with primary hyperparathyroidism. This retrospective cohort study aimed to examine whether contemporary patients operated for primary hyperparathyroidism have higher mortality than the general population, and whether mortality in these patients is associated with serum calcium concentration, adenoma weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…These mechanisms of diabetes mellitus and hypertension overlap substantially with the effects of PHPT on cardiovascular diseases. It has been reported that parathyroid hormone may cause endothelial dysfunction by inducing reactive oxygen species and in ammatory signals [5,42]. Therefore, consistent with previous studies, risk of cardiovascular diseases can be exacerbated in patients with PHPT, who also have diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These mechanisms of diabetes mellitus and hypertension overlap substantially with the effects of PHPT on cardiovascular diseases. It has been reported that parathyroid hormone may cause endothelial dysfunction by inducing reactive oxygen species and in ammatory signals [5,42]. Therefore, consistent with previous studies, risk of cardiovascular diseases can be exacerbated in patients with PHPT, who also have diabetes mellitus and hypertension.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to epidemiology, the prognostic factors for mortality and cardiovascular outcomes are crucial for the management of PHPT. Previous studies have reported an increased risk of cardiovascular diseases, cerebrovascular diseases, and mortality in patients with PHPT [5,6]. The risks are reported to decrease after parathyroidectomy [7] but remain higher than those in the general population [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival after parathyroidectomy has been recently reported from the US, UK, and Europe. [ 8 9 10 ] In these contemporary reports, the common finding is comparable mortality with respect to the general population. However, higher mortality rates in patients with symptomatic (associated with complications) or severe disease (serum calcium exceeding 10.8 mg/dl) have been reported even in these countries.…”
Section: B Ackgroundmentioning
confidence: 98%